DIFFERENCE OF MODERATE AND HARD-BRISTLED TOOTHBRUSH IN PREVENTING PLAQUE AMONG SCHOOL CHILDREN - Udin, Karsum; Santoso, Bedjo; Rahmawati, Ida; Sari, Emilda; Dedy, Dedy (Proceedings of the International Conference on Applied Science and Health, 2017)
Background: Oral health is very important, some oral and dental problems occur because we do not maintain oral hygiene and teeth. Plaque is a major etiologic factor of caries and periodontal disease. Efforts to prevent plaque buildup is called plaque control, by mechanical, chemical and natural, mechanical ventilation is a tooth brush. In general, the bristles are soft, moderate, and hard. Aims: This research aims to know the differences using a moderate and hard-bristled toothbrush against plaque. Methods: This is a quasi-experiment with pretest-post-test control group design between the bristles medium and hard bristles using independent test T-test.Â Conclusion: There is a difference of tooth brushing plaque by using the medium tough and hairbrush medium tough hairbrush and hairy on the students of class VII B and VII C in Public Junior High School 3 Banjarbaru. The use of hard bristled toothbrushes is better 72.22% than the use of medium toothbrushes is only 47.37%. But a hard hairy toothbrush can cause gums to drop (recession gingival) if done continuously.Â